Brand Image Theoretical Aspects - Margarita Išoraitė (Fakultas Ekonomi, Universitas Bangka Belitung, 2018)
The article analyzes the image of a brand and a brand image, brand value assessment methods, brand value, and benefits. A brand is a word or phrase that identifies and separates goods belonging to one person from belonging to another person. A brand is one of the elements of marketing, advertising. High-quality brand brings significant benefits to the manufacturer or the trader. A brand name may consist of a brand name and a brand symbol. There is several brand value evaluation model analyze in the article, like capital market-oriented brand value model, Aaker's brand value model, the Interbrand Brand Assessment Methodology, which helps evaluate brand value and benefit.